Risk Exposure and Risk Management of UK Non-life Insurance Company - Hu, Qiong (2010)
Risk cannot be removed completely but can be transferred. Insurance has been widely accepted and utilized as one risk transfer instrument by the public. Charging for certain amount of insurance premiums, insurers bear all the risk has been insured against by their clients and pay insurance claims when misfortunes occur. As any other business entities, insurers also have to face uncertainties. As a result, insurers have to deal with complex risks brought by their clients and themselves even under favorable economic conditions. Exposed to persistent turbulent economic conditions, risk management practices of insurers can be complex and difficult.